2018
DOI: 10.4028/www.scientific.net/kem.789.20
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Bag Waste on Hotmixture Asphalt as Modifier

Abstract: Indonesia is the second largest country to contribute plastic marine debris in the world. Onthe other hand, Indonesia is facing pavement problem due to various reasons, so it needs to improvethe pavement quality and performance. The addition of plastic waste to the hot mix asphalt (HMA)actually have beneficial effect to improve the pavement quality. Utilization of plastic waste in roadconstruction is conducted by incorporating the plastic waste into the asphalt mixture as an additivewith dry or wet mix process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Overall, the rutting resistance was observed to improve with the addition of both the LDPE and LLDPE plastics, as evident in Figure 7 and Table 4. A similar reduction in rutting with the addition of the LDPE and LLDPE plastics was reported by several studies ( 11 , 21 ). Also, the creep slope of the rutting plot was found to reduce with the increase in the amount of plastic.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Overall, the rutting resistance was observed to improve with the addition of both the LDPE and LLDPE plastics, as evident in Figure 7 and Table 4. A similar reduction in rutting with the addition of the LDPE and LLDPE plastics was reported by several studies ( 11 , 21 ). Also, the creep slope of the rutting plot was found to reduce with the increase in the amount of plastic.…”
Section: Resultssupporting
confidence: 88%
“…A recent study conducted by Willis et al suggested using polyethylene (PE), that is, LDPE, LLDPE, and HDPE in the production of asphalt mixes, as other plastics can produce toxic gases or are incompatible with asphalt mixes ( 6 ). Several studies have evaluated the basic properties, namely melting point, decomposition point, relative density, and particle sizes of PE plastics for potential use in asphalt mixes ( 7 11 ). Typically, the melting points and decomposition temperatures of the PE plastic used in asphalt research are in the range of 100°C to 120°C and 270°C to 350°C, respectively ( 7 , 12 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term performance Building roads from recycled plastic is still a nascent technology worldwide due to challenges hindering its development; hence, small stretches of plastic roads of less than 1 km have been built in many countries as prototypes to assess the real-time performance of plastic roads. [42][43][44][45] However, given that the oldest plastic roads built under controlled conditions are less than 8 years old and that asphalt roads are built to last for 20 years, the long-term performance of plastic roads remains unclear. Many standards are used worldwide to empirically test bitumen and asphalt materials under laboratory conditions 46 ; however, these conditions are not necessarily representative of real circumstances in the field.…”
Section: Performance Safety and Environmental Impacts Of Plastic Roadsmentioning
confidence: 99%